1989
DOI: 10.1042/bj2600121
|View full text |Cite
|
Sign up to set email alerts
|

Sweet tastants stimulate adenylate cyclase coupled to GTP-binding protein in rat tongue membranes

Abstract: Sucrose and other saccharides, which produce an appealing taste in rats, were found to significantly stimulate the activity of adenylate cyclase in membranes derived from the anterior-dorsal region of rat tongue. In control membranes derived from either tongue muscle or tongue non-sensory epithelium, the effect of sugars on adenylate cyclase activity was either much smaller or absent. Sucrose enhanced adenylate cyclase activity in a dose-related manner, and this activation was dependent on the presence of guan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(79 citation statements)
references
References 39 publications
5
73
1
Order By: Relevance
“…A member of the mammalian Gα subfamily, Gs, stimulates adenylyl cyclase, thus elevating cAMP concentrations [78,79]. This cAMP signal transduction pathway has been shown to be involved in sugar perception [84][85][86]. Additionally, the Gα subunit of the taste receptor-specific G-protein gustducin is required for mammalian behavioral response to bitter and sweet compounds [87].…”
Section: Signal Transductionmentioning
confidence: 99%
“…A member of the mammalian Gα subfamily, Gs, stimulates adenylyl cyclase, thus elevating cAMP concentrations [78,79]. This cAMP signal transduction pathway has been shown to be involved in sugar perception [84][85][86]. Additionally, the Gα subunit of the taste receptor-specific G-protein gustducin is required for mammalian behavioral response to bitter and sweet compounds [87].…”
Section: Signal Transductionmentioning
confidence: 99%
“…For the rat, an adenylate cyclase stimulated by sweet agents was reported (Striem et al, 1989), and intact taste cells were recently shown to generate cAMP in response to exposure with sucrose (Striem et al, 1990). In the frog, cAMP caused an inhibition of outward current and a depolarization in ~50% of the TRCs investigated (Avenet and Lindemann, 1987b).…”
Section: Response To Sweetmentioning
confidence: 99%
“…The earliest identified tastetransduction stream involved the second messenger cyclic adenosine monophosphate (cAMP). Decades ago, Striem et al [101] reported that treating membranes derived from the anterior surface of rat tongues with sucrose stimulated adenylyl cyclase, implying the presence of G as proteins and Focussed search with primers based on synaptic glutamate receptors cAMP pathways in taste. These studies have been replicated and extended, using intact taste tissue [102].…”
Section: Second-messenger Cascades and Taste Gpcrsmentioning
confidence: 99%